Democratic Republic of Sao Tome and Principe : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of Sao Tome and Principe. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) for the Democratic Republic of Sao Tome and Principe. All quantitative performance criteria and structural benchmarks for end-December 2006 were met. Progress continues on structural reform, albeit sometimes slower than originally envisaged. The authorities agreed to strengthen policy implementation to bring inflation further down. IMF staff recommends completion of the fourth review based on the country's performance and policy commitments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet